Pengaruh Konseling Obat Terhadap Pengetahuan dan Sikap Pasien Asma di Rawat Jalan RS. Advent Medan - Ari Anti Br Bangun, Putri; Malem Br Karo, Reh; Halimatussa’diyah Pakpahan, Enni; Neswita, Elfia (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Counseling by pharmacists is a beneficial activity for patients. Through counseling, pharmacists can provide advice that broadens patients' knowledge of the disease and the medications they are taking. In addition, counseling can also improve patient compliance in undergoing drug therapy that they are undergoing. This good knowledge and adherence will have a positive impact on achieving the patient's treatment goals.This study used experimental methods with pre-experimental designs, especially pretest-posttest designs in one group. The study was conducted on asthma patients at Medan Adventist Hospital, with prospective data collection using questionnaires, involving 50 respondents. Analysis of the data of this study shows the effect of drug counseling on the knowledge and attitudes of asthma patients. Data analysis stages include crosstab, chi-square, paired-sample t-test, pearson product moment for validity and reliability tests, as well as simple linear regression.Test results showed that gender, age, and occupation did not have a significant relationship with patients' knowledge and attitudes, while education showed a significant association. Although sex, age, and occupation did not show significant associations, these characteristic data remained valid as supporting information in drug counseling for asthma patients. The majority of respondents aged 15-25 years (40%), are students (26%), and have S1 education (56%), indicating that asthma is common in this age group and occupation due to exposure to allergens, extreme physical activity, cigarette smoke, weather changes, polluted air, and respiratory infectionsr.